2018
DOI: 10.1002/jper.17-0554
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant soft tissue inflammatory parameters and crestal bone loss among waterpipe (narghile) smokers and never‐smokers with and without type 2 diabetes mellitus

Abstract: Peri-implant soft tissue inflammatory parameters and CBL were comparable among WS and NS with T2DM. Among individuals without T2DM, these parameters were worse among WS than NS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
(71 reference statements)
0
21
0
Order By: Relevance
“…Of these, eight studies were further excluded. After the final stage of selection, four studies were included and processed for data extraction (ĸ score: 0.97 [0.94‐1.00]) . All studies were performed at university hospitals .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, eight studies were further excluded. After the final stage of selection, four studies were included and processed for data extraction (ĸ score: 0.97 [0.94‐1.00]) . All studies were performed at university hospitals .…”
Section: Resultsmentioning
confidence: 99%
“…After the final stage of selection, four studies were included and processed for data extraction (ĸ score: 0.97 [0.94‐1.00]) . All studies were performed at university hospitals . The PRISMA flowchart of the search process is presented in Figure , with reasons of exclusion indicated …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial body of evidence in Saudi population has shown that waterpipe smokers (WS) have increased prevalence of peri-implant diseases and that the disease is worse than NS. 10,11 In a recent pilot studies conducted by Al-Aali et al 12 and…”
Section: Introductionmentioning
confidence: 97%
“…Another form, that is, waterpipe smoking also known as hookah , sheesha , or narghile smoking appears to be overtaking cigarette smoking in popularity, and public tolerance of this habit is becoming greater. A substantial body of evidence in Saudi population has shown that waterpipe smokers (WS) have increased prevalence of peri‐implant diseases and that the disease is worse than NS …”
Section: Introductionmentioning
confidence: 99%